2011
DOI: 10.1590/s0104-11692011000400005
|View full text |Cite
|
Sign up to set email alerts
|

Content validity of the short version of the subscale of the State-Trait Anxiety Inventory (STAI)

Abstract: Inmaculada Martínez-Durá 5The goal was to describe the content validity of a short version of the state subscale of Validez de contenido de versión corta de la subescala del Cuestionario State-Trait Anxiety Inventory (STAI)Se tuvo por objetivo describir la validez de contenido de una versión corta de la subescala Estado del State-Trait Anxiety Inventory (STAI) de Spielberger, a partir de la versión original adaptada al español, en pacientes españoles con ventilación mecánica invasora (VMI). La muestra fue in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…19 Although the Spanish version of the original Spielberger scale (STAI-E) has been used in numerous studies in Spain, none of the short versions has been used in this country. In a previous study, 27 we concluded that the short version of the STAI-E developed by Chlan et al showed good content validity for Spanish patients receiving IMV.…”
mentioning
confidence: 68%
“…19 Although the Spanish version of the original Spielberger scale (STAI-E) has been used in numerous studies in Spain, none of the short versions has been used in this country. In a previous study, 27 we concluded that the short version of the STAI-E developed by Chlan et al showed good content validity for Spanish patients receiving IMV.…”
mentioning
confidence: 68%
“…The inclusion criteria were subjects with a need for orthodontic treatment (self-perceived) and about to undergo fixed orthodontic appliance therapy (straight-wire technique). Patients were excluded if they had severe malocclusion; previous orthodontic treatment; recent toothache; periodontal diseases (periodontal pocket > 3 mm); untreated dental caries (cavitated lesions); infectious diseases and/or systemic diseases; or overanxiety, as confirmed by the Trait-Anxiety Inventory (T-AI) score (male ≥56; female ≥57) and the State-Anxiety Inventory (S-AI) score [ 25 ] (male ≥53; female ≥55).…”
Section: Methodsmentioning
confidence: 99%
“…The ST-AI is a 40-item Likert scale which assesses separate dimensions of “state” anxiety (items l–20) as well as “trait” anxiety (items 21–40) [ 25 ]. Pain intensity was measured by a 100 mm visual analogue scale (VAS) ranging from 0 = no pain at all to 10 = worst pain possible [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is a methodological study which has adopted the recommended psychometric procedures (7)(8) to construct the EAPDI, which includes three specific points (the theoretical, the empirical and the analytic); however, in this study we have only included the theoretical and analytical poles, in relation to the apparent and content validity, which are stages also carried out by other authors (9) .…”
Section: Methodsmentioning
confidence: 99%